The PHILOSOPHICAL VALUE OF MARABOSE FESTIVAL IN THE CONTEXT OF MULTICULTURAL EDUCATION - Astria, Windi; Munir, Ahmad; Abdullah, Muhaimin; Ahmadi, Anas (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
The Marabose Festival is an annual cultural event in South Halmahera Regency, North Maluku, that serves as a platform for showcasing the region’s rich cultural diversity. The festival, which involves various indigenous and immigrant tribes, facilitates the preservation and transmission of cultural values through performances, rituals, and art exhibitions. Beyond its ceremonial function, the Marabose Festival plays a critical role in character education, intergenerational transmission of local wisdom, and dakwah efforts. This study aims to analyze the philosophical values inherent in the Marabose Festival within the framework of multicultural education, guided by the educational philosophy of Ki Hajar Dewantara. A qualitative descriptive approach was used, with data collected through document analysis, participatory observation, and in-depth interviews with key stakeholders, including festival organizers, educators, students, and parents. The findings suggest that the festival’s values align with Ki Hajar Dewantara’s Tri Center of Education, Merdeka Belajar, and Among Systems. The festival fosters cognitive growth by enhancing knowledge of ethnic and cultural diversity, encourages the development of an affective attitude towards tolerance and respect, and nurtures psychomotor skills through active participation in cultural preservation. Furthermore, the festival serves as an effective tool for communication and dakwah, promoting intercultural dialogue and fostering unity in diversity. In conclusion, the Marabose Festival offers a unique opportunity for integrating multicultural education based on local wisdom into the formal education system, promoting cultural identity, tolerance, and communal harmony.